Thioredoxin system in colorectal cancer: Its role in carcinogenesis, disease progression, and response to treatment - Abdullah, Nurul Akmaryanti; Md Hashim, Nur Fariesha; Muhamad Zakuan, Noraina; Chua, Jia Xin (Elsevier, 2024)
The thioredoxin system is essential for many physiological processes, including the maintenance of redox signalling pathways. Alterations in the activity, expression and interactions with other signalling pathways can lead to protective or pathophysiological responses. Thioredoxin and thioredoxin reductase, the two main components of this system, are often overexpressed in cancer, including colorectal cancer. This overexpression is often linked with tumour progression and poor outcomes. This review discusses the role of the Trx system in driving colorectal carcinogenesis and disease progression, as well as the challenges of targeting this system. Additionally, the recent advancements in the development of novel and effective thioredoxin inhibitors for colorectal cancer are also explored.